Genome-wide siRNA screen reveals amino acid starvation-induced autophagy requires SCOC and WAC - McKnight, Nicole C; Jefferies, Harold B J; Alemu, Endalkachew A; Saunders, Rebecca E; Howell, Michael; Johansen, Terje; Tooze, Sharon A (The EMBO journal, 2012)
Autophagy is a catabolic process by which cytoplasmic components are sequestered and transported by autophagosomes to lysosomes for degradation, enabling recycling of these components and providing cells with amino acids during starvation. It is a highly regulated process and its deregulation contributes to multiple diseases. Despite its importance in cell homeostasis, autophagy is not fully understood. To find new proteins that modulate starvation‐induced autophagy, we performed a genome‐wide siRNA screen in a stable human cell line expressing GFP–LC3, the marker‐protein for autophagosomes. Using stringent validation criteria, our screen identified nine novel autophagy regulators. Among the hits required for autophagosome formation are SCOC (short coiled‐coil protein), a Golgi protein, which interacts with fasciculation and elongation protein zeta 1 (FEZ1), an ULK1‐binding protein. SCOC forms a starvation‐sensitive trimeric complex with UVRAG (UV radiation resistance associated gene) and FEZ1 and may regulate ULK1 and Beclin 1 complex activities. A second candidate WAC is required for starvation‐induced autophagy but also acts as a potential negative regulator of the ubiquitin‐proteasome system. The identification of these novel regulatory proteins with diverse functions in autophagy contributes towards a fuller understanding of autophagosome formation. A genome‐wide siRNA screen identifies autophagy regulators. The Golgi protein SCOC regulates the interaction between ULK1 kinase and the Beclin 1 complexes in a nutrient‐dependent manner; WAC enhances starvation‐induced autophagy, while inhibiting the ubiquitin‐proteasome system.